Strength and neuromuscular adaptation following one, four, and eight sets of high intensity resistance exercise in trained males - Marshall, P. W. M.; McEwen, M.; Robbins, D. W. (European Journal of Applied Physiology, 2011)
The optimal volume of resistance exercise to prescribe for trained individuals is unclear. The purpose of this study was to randomly assign resistance trained individuals to 6-weeks of squat exercise, prescribed at 80% of a 1 repetition-maximum (1-RM), using either one, four, or eight sets of repetitions to failure performed twice per week. Participants then performed the same peaking program for 4-weeks. Squat 1-RM, quadriceps muscle activation, and contractile rate of force development (RFD) were measured before, during, and after the training program. 32 resistance-trained male participants completed the 10-week program. Squat 1-RM was significantly increased for all groups after 6 and 10-weeks of training (P < 0.05). The 8-set group was significantly stronger than the 1-set group after 3-weeks of training (7.9% difference, P < 0.05), and remained stronger after 6 and 10-weeks of training (P < 0.05). Peak muscle activation did not change during the study. Early (30, 50 ms) and peak RFD was significantly decreased for all groups after 6 and 10-weeks of training (P < 0.05). Peak isometric force output did not change for any group. The results of this study support resistance exercise prescription in excess of 4-sets (i.e. 8-sets) for faster and greater strength gains as compared to 1-set training. Common neuromuscular changes are attributed to high intensity squats (80% 1-RM) combined with a repetition to failure prescription. This prescription may not be useful for sports application owing to decreased early and peak RFD. Individual responsiveness to 1-set of training should be evaluated in the first 3-weeks of training.